2016
DOI: 10.1016/j.ajem.2016.01.028
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of an esophageal heat transfer device into a therapeutic hypothermia protocol: A prospective evaluation

Abstract: Using the EHTD, our patient population attained goal temperatures in one hour, the volume of ice-cold saline required to attain this cooling rate was decreased by one-third, and experienced a low percentage of time outside target temperature range and no major adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
1
24
1
Order By: Relevance
“…Accordingly, cooling rates in the present study met the recommendations of rapid cooling with cooling rates between 2.8 and 3.0°C/h. However, we must not forget the fact that this was an experimental study with an average body weight of 27-30kg, which is approximately half of that used in the studies of Markota and Kulstad [15, 23]. Eventually, extrapolation of data of this study to experimental and clinical cooling rates is difficult, which is a limitation of this study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Accordingly, cooling rates in the present study met the recommendations of rapid cooling with cooling rates between 2.8 and 3.0°C/h. However, we must not forget the fact that this was an experimental study with an average body weight of 27-30kg, which is approximately half of that used in the studies of Markota and Kulstad [15, 23]. Eventually, extrapolation of data of this study to experimental and clinical cooling rates is difficult, which is a limitation of this study.…”
Section: Discussionmentioning
confidence: 93%
“…Scientific evidence hints towards neuroprotection by rapid cooling after OHCA with 1–2°C/h [12]. Recently, Markota et al reported a cooling rate of 1.12°C/h in a prospective evaluation of OHE after OHCA [23]. A cooling rate of 1.3°C/h was reached by OHE in an experimental study in pigs that did not suffer cardiac arrest but underwent a TTM-protocol [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel esophageal cooling device helps to achieve rapid induction in patients with post cardiac arrest [103]. According to its noninvasive property, it is also feasible for fever control in intensive care unit [104].…”
Section: The Novel Cooling Methodsmentioning
confidence: 99%
“…Mathematical models and animal studies strongly support the efficacy and safety of the ECD [11][12][13]. In 2 series recently published, potential side-effects of ECD were not precisely evaluated [14,15]. Additionally, ECD was always associated with other cooling methods such as the use of large volume of cold fluids, despite that this cooling method is no longer recommended according to recent international guidelines [16].…”
Section: Introductionmentioning
confidence: 99%